Plasma alterations in Immunoglobulin G (IgG), Immunoglobulin M (IgM) and immunoglobulin A (IgA) , serum transferrin (TFN), serum albumin (ALB) and prealbumin (PA), Interleukin (IL-6) and serum C-reactive protein (CRP) after immune-type enteral nutrition s: Plasma alterations in Immunoglobulin G (IgG), Immunoglobulin M (IgM) and immunoglobulin A (IgA) , serum transferrin (TFN), serum albumin (ALB) and prealbumin (PA), Interleukin (IL-6) and serum C-reactive protein (CRP) - Cui, Xiaoxu; Wu, Haiping (Journal of Medical Biochemistry, 2025)
Objective: To explore the effects of immune-type enteral nutrition support on postoperative recovery and nutritional status and Plasma alterations in Immunoglobulin G (IgG), Immunoglobulin M (IgM) and immunoglobulin A (IgA) , serum transferrin (TFN), serum albumin (ALB) and prealbumin (PA), Interleukin (IL-6) and serum C-reactive protein (CRP) of patients undergoing radical resection of colon cancer. Methods: From January 2023 to December 2024, 106 patients with colon cancer who underwent radical resection of colon cancer were selected as the study objects. Patients were divided into control group (CG) and observation group (OG) according to random number table method. The CG received routine nursing intervention plus routine parenteral nutrition support. The OG implemented high-quality nursing intervention based on the CG plus immune-type enteral nutrition support. The postoperative recovery time, nutritional indicators, immune function, inflammatory response, quality of life, incidence of complications along with nursing satisfaction in 2 groups were compared. Results: In comparison with the CG, the the recovery time of bowel sound, time of exhaust gas, time of defecation, time of getting out of bed and hospital stay in the OG presented shorter (P<0.05), the incidence of complications in the OG exhibited lower (P<0.05), and the nursing satisfaction in the OG exhibited better (P<0.05). After intervention, TFN, PA and ALB levels in the OG presented elevation when comparing with the CG (P<0.05). After intervention, IgG, IgA and IgM levels in the OG presented elevation when comparing with the CG (P<0.05). After intervention, CRP and IL-6 levels in the OG presented reduction when comparing with the CG (P<0.05). After intervention, QLQ-C30 scores in the OG presented elevation when comparing with the CG (P<0.05). Conclusion: High-quality nursing combined with immune-type enteral nutrition support can promote the postoperative recovery, enhance nutritional status and immune function, along with reduce the incidence of complications in patients undergoing radical resection of colon cancer.